Correlation Between Six Minutes Walk Distance with Blood Glucose Level in Pilgrims at Saiful Anwar General Hospital Malang - V Kurniawati (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Background: Chronic, metabolic and cardiovascular diseases are still have higher incidences .....